2017
DOI: 10.1016/j.compedu.2017.04.012
|View full text |Cite
|
Sign up to set email alerts
|

On the quest for validity: Testing the factor structure and measurement invariance of the technology-dimensions in the Technological, Pedagogical, and Content Knowledge (TPACK) model

Abstract: Highlights  A general TPACK factor and a specific TK can be disentangled.  The T-dimensions in the TPACK are highly correlated (ρ > .80).  Measurement invariance across gender and educational track can be established.  Significant gender differences in the T-dimensions exist.  In conclusion, the TK factor stands out among all T-dimensions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0
10

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(91 citation statements)
references
References 86 publications
3
60
0
10
Order By: Relevance
“…Koh et al (2010) revealed the importance of the gender factor in the TPACK perceptions of pre-service students. This study is consistent with other studies like that of Markauskaite (2006), who showed that male teachers are more confident in using computers than their female colleagues; Lin et al (2013), who found higher PK for female teachers but lower TK; and Scherer et al (2017), who found that for all the T-factors, males report higher competency than females. However, thinking gender as predictor of TPACK can be interpreted as an essentialist view of the knowledge determinants.…”
Section: Theoretical Background 21 Tpack Modelsupporting
confidence: 92%
“…Koh et al (2010) revealed the importance of the gender factor in the TPACK perceptions of pre-service students. This study is consistent with other studies like that of Markauskaite (2006), who showed that male teachers are more confident in using computers than their female colleagues; Lin et al (2013), who found higher PK for female teachers but lower TK; and Scherer et al (2017), who found that for all the T-factors, males report higher competency than females. However, thinking gender as predictor of TPACK can be interpreted as an essentialist view of the knowledge determinants.…”
Section: Theoretical Background 21 Tpack Modelsupporting
confidence: 92%
“…Empirically, Abbitt () found statistically significant correlations between preservice teachers' TPACK subscale scores (TK, PK, TPK, TCK, TPCK), collected from Schmidt et al 's survey, and their self‐efficacy beliefs, collected from Wang et al 's survey. Moreover, researchers have viewed Schmidt et al 's survey as capturing teachers' self‐efficacy beliefs related to TPACK domains (Scherer et al , ). In addition, technology integration researchers have found positive correlations between preservice teachers' technology integration self‐efficacy beliefs and their intentions to use technology in future classrooms (Banas & York, ; Celik & Yesilyurt, ; Lee & Lee, ; Sang, Valcke, van Braak, & Tondeur, ).…”
Section: The Proposed Approachmentioning
confidence: 99%
“…Empirical evidence has suggested the need to pay extra attention to technology‐related knowledge (TK, TCK, TPK, TPCK) when examining preservice teachers' TPACK (Chai et al , ; Mouza et al , ). More recently, Scherer and colleagues () explored factor structures with TK, TCK, TPK and TPCK data from preservice teacher in Flanders and found that a nested factor structure performed the best. In particular, all items loaded on one general factor (TPACK‐general) and the TK items additionally loaded on another (TK), highlighting TK as the unique dimension to be captured apart from the other technology‐related knowledge (TCK, TPK, TPCK), which failed to be empirically disentangled.…”
Section: The Proposed Approachmentioning
confidence: 99%
See 2 more Smart Citations